Controlling factors for the spatial variability of soil magnetic susceptibility across England and Wales - Blundell, A.; Dearing, J. A.; Boyle, J.; Hannam, Jacqueline A. (Elsevier Science B.V., Amsterdam., 2009)
We review the nature and importance of soil factors implicated in the formation of secondary ferrimagnetic minerals in soils and palaeosols worldwide. The findings are examined with respect to temperate regions through a comprehensive analysis of over 5000 samples of surface soil from England and Wales taken from a 5 × 5 km grid. Over 30 soil and environmental attributes are considered for each sample as proxies for soil forming factors. Measurements of low field magnetic susceptibility (mass specific) and frequency dependent susceptibility (mass specific and percentage) on each sample provide estimates of the concentration and grain size of ferrimagnetic minerals. Maps of soil magnetism across England and Wales show non-random distributions and clusters. One subset of data is clearly linked to contamination from atmospheric pollution, and excluded from subsequent analyses. The concentration of ferrimagnetic minerals in the non-polluted set is broadly proportional to the concentration of minerals falling into the viscous superparamagnetic domain size range (~ 15–25 nm). This set shows clusters of high magnetic concentrations particularly over specific parent materials such as schists and slates, mudstones and limeston
Keywords: soil magnetism; magnetic susceptibility; frequency-dependence; soil forming factors; England and Wales